Morphological and Molecular Characterization of Paragonimus Species Isolated from Freshwater Crabs in Southern Yunnan, China. (31st December 2021) - Shu, Qiu-Hong; Yang, Yang; Wang, Miao-Miao; Li, Shu-De; Tian, Ming; Bai, Wen-Wei; Meng, Yong; He, Shu-Mei-Qi; Wang, Wen-Lin
Abstract : Paragonimus species are highly prevalent in various regions of China. The study's objective is to isolate and identify Paragonimus from natural habitats and compare the phylogenetic diversity of Paragonimus in southern Yunnan province, China. Metacercariae of Paragonimus was isolated from crabs, and morphologic identification was performed by microscopy. Metacercariae were injected into experimental Paragonimus free Sprague Dawley rats. After 114 days, adult worms and eggs were isolated from multiple organs. Morphologic identification confirmed the initial identification. DNA was extracted from 5 adult worms, and molecular characterization was performed by amplification and sequencing of CO1 and ITS2 regions, followed by phylogenetic analysis. Out of 447 crabs captured, 186 crabs were found to be infected. A total of 4 species of Paragonimus was observed from naturally infected crabs. Paragonimus microrchis (2), Paragonimus heterotremus (1), Paragonimus proliferus (1), and Paragonimus skrjabini (1) were isolated and identified. A total of 32 sequences were downloaded from the National Center for Biotechnology Information, and 5 sequences generated in the study were used for phylogenetic analysis. In the phylogenetic tree of the CO1 gene, Paragonimus proliferus, Paragonimus heterotremus, and Paragonimus skrjabini were clustered with the same species, and the confidence values of their branches were >95%. A congruent phylogenetic relationship was observed with the ITS2 phylogenetic tree. In the phylogenetic tree constructed with the combined dataset of CO1 and ITS2 datasets, Paragonimus proliferus, Paragonimus heterotremus, and Paragonimus skrjabini clustered with the same species, and their branch confidence values were >94%. Paragonimus microrchis clustered with Paragonimus bangkokensis in both datasets. Phylogenetic analysis revealed robustness of the double loci method as against the single-locus method with either CO1 or ITS2 alone. Paragonimus species isolated from the southern Yunnan province, China, was phylogenetically diverse, and the analysis revealed the clustering of multiple species of Paragonimus isolated from different geographic locations.